A review of Rhynchortalia Crotch (Coleoptera: Coccinellidae: Ortaliinae) - Poorani, J.; Ślipiński, Adam (Zootaxa, 2010)
The endemic Australasian genus Rhynchortalia Crotch (1874) is reviewed. Twelve species are described, keyed and illustrated, including the type species, R. insueta Crotch, and eleven new species (Rhynchortalia australis, R. viridis, R. wau, R. papuana, R. iongai, R. purpurea, R. similis, R. riedeli, R. anupama, R. iba, and R. moresby, spp. n.).